The C5 Convertase Is Not Required for Activation of the Terminal Complement Pathway in Murine Experimental Cerebral Malaria - Ramos, Theresa N. (American Society for Biochemistry and Molecular Biology, 2012)
Cerebral malaria (CM) is the most severe manifestation of clinical malaria syndromes and has a high fatality rate especially in the developing world. Recent studies demonstrated that C5(−/−) mice are resistant to experimental CM (ECM) and that protection was due to the inability to form the membrane attack complex. Unexpectedly, we observed that C4(−/−) and factor B(−/−) mice were fully susceptible to disease, indicating that activation of the classical or alternative pathways is not required for ECM. C3(−/−) mice were also susceptible to ECM, indicating that the canonical C5 convertases are not required for ECM development and progression. Abrogation of ECM by treatment with anti-C9 antibody and detection of C5a in serum of C3(−/−) mice confirmed that C5 activation occurs in ECM independent of C5 convertases. Our data indicate that activation of C5 in ECM likely occurs via coagulation enzymes of the extrinsic protease pathway.